Autonomy as a possible solution to self-determination disputes : Does it really work? - Abushov, Kavus (Brill Nijhoff, 2015)
The focus of this article concerns conditions in which autonomy may become a solution to a secessionist conflict, and why it works in certain cases but fails in others. It explores whether autonomy can be a generally applicable solution to complex self-determination disputes, or whether the cases of successful implementation are too specific, depending on specific circumstances. In other words, why has autonomy been accepted in certain cases, but refused in others? I analyze which entities are entitled to the right of secession, proceed to cases where autonomy has been a solution to secession, and finally discuss cases where autonomy-based solutions have failed. There is also some discussion of the conditions for an effective functioning of autonomy and power-sharing. Before proceeding to exploring the above-mentioned questions related to autonomy and power sharing, the legal nature of the right of self-determination and secession is explored.
International journal on minority and group rights.
Keywords: Minorities -- Civil rights -- Periodicals.; Human rights -- Periodicals.; Autonomy -- Periodicals.